Larval identities of Ansonia hanitschi Inger, 1960 (Amphibia: Bufonidae) and Polypedates colletti (Boulenger, 1890) (Amphibia: Rhacophoridae) from East Malaysia (Borneo) - Haas, A.; Das, I. (Deutsche Gesellschaft für Herpetologie und Terrarienkunde e.V. (DGHT), 2008)
We describe the tadpoles of Ansonia hanitschi Inger, 1960 and Polypedates colletti (Boulenger, 1890) from East Malaysia, Borneo. The morphological description is supplemented by photos of living specimens and SEM images of external and internal features. Identification was based on morphological and genetic characters (16S rRNA). The tadpole of A. hanitschi is among the largest tadpoles described for the genus Ansonia from Borneo. This suctorial-rheophilous tadpole has been collected from fast-flowing rocky streams, in association with foaming currents. The tadpole of P. colletti is redescribed due to uncertainties about its identity and lack of photographic evidence in previous descriptions. It is an inhabitant of stagnant waters, living in and on flooded leaf litter accumulations.